Teoria de redes complexas e o poder de difus\~ao dos municípios - Bernardo Assunç\~ao Mello; Daniel Oliveira Cajueiro; Luiz Henrique Batistuta Gomide; Roberta Vieira; Rogério Boueri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper aims at contributing to the decision-making regarding the allocation of public resources under the Federal Legislative Power. The focus of the paper was to construct criteria that could help elect the municipal legislative council in each micro-region that has the greatest power of dissemination and influence in the legislative process of surrounding councils. To this end, we constructed the indicator of municipality centrality based on the theory of complex networks.
Keywords: C44; C63; R19; 330